Numerical analysis of static behavior of caisson-type quay wall deepened by grouting rubble-mound - Anh-Dan Nguyen; Young-Sang Kim; Gyeong-O Kang; Hui-Jin Kim (International Journal of Geo-Engineering, 2021)
Abstract Caisson type gravity quay wall is a common structure used in the coastal regions. However, many of the existing quay walls constructed in the past are becoming obsolete. Therefore, the main goal of this study is to enhance the performance of these quay walls by increasing the front water depth. To deepen the water depth, a special grout type is ejected to solidify the rubble mound under the caisson toe, then excavating a part of the rubble placed in front of the caisson to the designed level. Various cases with different shapes and dimensions are proposed to optimize the grouted area. Based on the examination of stability and construction feasibility, the reasonable geometry and area of grouted rubble can be selected. In addition, the numerical analysis is performed by the Finite Element Method (FEM) program (PLAXIS 2D) to expect the behavior of the quay wall and grouted rubble. The results demonstrate that after upgrading, the maximum contact stress between caisson and rubble mound increases sharply, but the stress at the bottom of grouted rubble does not change in comparison prior to innovation. The analysis also indicates that when the Hardening Soil (HS) model is applied, the displacement of the quay wall is higher than that of the Mohr–Coulomb soil (MC) model.